PHARMACEUTICAL PARTNERSHIPS IN THE DEVELOPMENT OF NEW PHARMACEUTICALS - A. L. Bulgakov; R. V. Kosmakov (Фармация и фармакология (Пятигорск), 2018)
This article examines the causes for creating alliances between manufacturers and drug developers. The attention has also been paid to the classification of such partnerships depending on the level of integration. The classification is necessary for further study of relations in the alliances. It is important to understand how economically effective and justified such partnerships are. The aim of the study is to determine the reasons for creating partnerships between drug developers and manufacturers, and to work out a classification of partnerships in the field of pharmacology. Materials and methods. The study analyzes existing alliances, partnerships of Big Pharma companies such as Bayer AG, Merck & Co, Pfizer. Results and discussion. The variety of forms of partnerships allows all participants in this market to get from cooperation the benefits they need. Some seek to reduce risk, others look forward to gaining access to new research opportunities, the third seek to share knowledge for greater productivity. However, there is always the opposite side, they have to sacrifice something to get a market advantage. For example, increased integration leads to a reduction in the risk of drug creation, but also leads to a decrease in the company’s independence. Conclusion. The results of this study can be used later in the study of the financial effectiveness of pharmaceutical partnerships, as well as in exploring the causes of alliances’ collapses. Any partnership has its value and can be considered as an intangible asset of the company. However, at the moment, there is no universal way of assessing this type of active assets, therefore, classification is a key step in creating a model for determining the value of a partnership.